Neuronal antibodies in pediatric epilepsy: Clinical features and long‐term outcomes of a historical cohort not treated with immunotherapy. (21st March 2016) - Wright, Sukhvir; Geerts, Ada T.; Jol‐van der Zijde, Cornelia Maria; Jacobson, Leslie; Lang, Bethan; Waters, Patrick; van Tol, Maarten J. D.; Stroink, Hans; Neuteboom, Rinze F.; Brouwer, Oebele F.; Vincent, Angela
Summary: Objective: In autoimmune encephalitis the etiologic role of neuronal cell‐surface antibodies is clear; patients diagnosed and treated early have better outcomes. Neuronal antibodies have also been described in patients with pediatric epilepsy without encephalitis. The aim was to assess whether antibody presence had any effect on long‐term outcomes in these patients. Methods: Patients (n = 178) were recruited between 1988 and 1992 as part of the prospective Dutch Study of Epilepsy in Childhood; none received immunotherapy. Healthy age‐matched bone‐marrow donors served as controls (n = 112). All sera were tested for serum N ‐methyl‐d ‐aspartate receptor (NMDAR), alpha amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor, leucine rich glioma inactivated 1, contactin associated protein like 2 (CASPR2), contactin‐2, glutamic acid decarboxylase, and voltage gated potassium channel (VGKC)‐complex antibodies by standard techniques. No cerebrospinal fluid (CSF) samples were available. Results were correlated with clinical data collected over 15 years. Results: Seventeen patients (9.5%) were positive for VGKC complex (n = 3), NMDAR (n = 7), CASPR2 (n = 4), and contactin‐2 (n = 3), compared to three (3/112; 2.6%) healthy controls (VGKC complex [n = 1], NMDAR [n = 2]; p = 0.03; Fisher's exact test). Titers were relatively low (≤1:100 for cell‐surface antibodies), but 8 (47%) of the 17 positive samples bound to the surface of live hippocampal neurons consistent with a potential pathogenic antibody. Preexisting cognitive impairment was more frequent in antibody‐positive patients (9/17 vs. 33/161; p = 0.01). Fourteen antibody‐positive patients were treated with standard antiepileptic drugs (AEDs); three (17%) became intractable but this was not different from the 16 (10%) of 161 antibody‐negative patients. In 96 patients with available follow‐up samples at 6 and/or 12 months, 6 of 7 positive antibodies had disappeared and, conversely, antibodies had appeared for the first time in a further 7 patients. Significance: Neuronal antibodies were found at low levels in 9.5% of patients with new‐onset pediatric epilepsy but did not necessarily persist over time, and the development of antibodies de novo in later samples suggests they could be due to a secondary response to neuronal damage or inflammation. Moreover, as the response to standard AEDs and the long‐term outcome did not differ from those of antibody‐negative pediatric patients, these findings suggest that routine neuronal antibody testing is unlikely to be helpful in pediatric epilepsy. However, the higher incidence of preexisting cognitive problems in the antibody‐positive group, the CASPR2 and contactin‐2 antibodies in 7 of 17 patients, and the binding of 8 of 17 of serum samples to live hippocampal neurons suggest that neuronal antibodies, even if secondary, could contribute to the comorbidities of pediatric epilepsy.